Bale Mountains vegetation classification - Evangelista, Paul (Colorado State University. Libraries, 2012)
Vegetation cover for the Bale Mountains, Ethiopia. Field data and spatial environmental data were used with a classification and regression tree model to develop the map. The map is at 30 meter resolution and includes 12 different vegetation classes.
Natural Resource Ecology Laboratory (NREL)
Ethiopia Project
Keywords: land cover; Bale Mountains; Ethiopia; vegetation cover; map; Geographic Information Systems; GIS